(untitled) (Ukrainian Journal of Ophthalmology, 2025)
The Modern Surgery for Congenital Cataract in Children international conferences including master classes and live surgical demonstrations were conducted at the Filatov institute in 2003 and 2007 partly due to a keen interest of eye surgeons over the world in the subject and numerous unresolved problems in the field of pediatric surgery. The leading cataract surgeons, Charlotta Zetterström (Sweden), Yu.V. Takhtaev and K.B. Pershin (Russia), G. Tassinari (Italy) and N.F. Bobrova (Ukraine) participated in the first pediatric live surgical event in 2003 (Fig. 1). The audience watched the surgery course on a screen and used the opportunity to interact with surgeons, asking them questions and getting answers in real time (Fig. 2). No intraoperative or postoperative complications were recorded. The following day, postoperative status of the eyes with restored visual acuity was shown to the audience. Anyone who wished could use the slit lamp installed at the conference hall to examine the child who had undergone live surgery.